Avaliação da qualidade de cosméticos com ativo cafeína em bases galênicas gel e creme elaborado por farmácias magistrais na cidade de Campo Mourão - PR - Vogel, Eliane Maria (2020)
The beauty market evolution and the personal care have been constant in Brazil and all around the world. Beyond the cosmetic industry, the masterful pharmaceutical grouth and the technological evolution in the development and production of comesctics require the compliance of regulated directives to prevent quality risks and guarantee safety in the fabrication of a cosmetic.The microbiological control is substantial to a good cosmetic formulation because the high rate of microorganisms can cause allergies and rashes in the skin which may develop severe pathologies.Factors such as pH, colorimetry, viscosity and quantity of the cosmetic base active ingredient are essential to maintain formulation’s stability and homogeneity until the expiration date.A safe and effective cosmetic can be defined as the one which fulfil its purpose with low probability of causing harm, since the total absence of risks does not exist.To achieve the desirable results, the choice of raw material and base is as important as the interaction between the active ingredients of a cosmetic formula.Since there is a shortage of studies about the value of good practices in the cosmetic handling and fabrication, the present study has the objective to evaluate the quality control of cosmetics manufactured by handling pharmacies in Campo Mourão, state of Paraná, Brazil. The evaluated cosmetics are the ones that have caffeine as its active substance to treat cellulite. Thus, multiple analysis was carried such as microbiological, pH determination, colorimetry, quantification of the caffeine percentage and viscosity in cosmetics with gel and cream base that had 5% of active substance caffeine. In the microbiological analysis was found the presence of molds and yeasts above the levels allowed by the Brazilian Pharmacopoeia. The pH reduced over time, contributing for the acidification of the formulations. In the color parameter it was found that the F4 Pharmacy presented brown color in the gel and cream formulations. The caffeine percentage was in accordance with the specifications in all formulations and the viscosity stayed unchanged during the sample’s expiration date. To a better formula elaboration, it was found that it is important that handling pharmacies require staff’s commitment, as well as raw material analysis according to microbiological control regulations. In addition, the implementation of more restricted standards, a better raw material control and the quality inspection of final formulation of cosmetics increase the quality of the handled products made by handling pharmacies, favoring the final consumer.